Morphometric and Histological Study of Reproductive Organs of Indigenous Ewes: Sheep reproductive organs: age-related changes - Sultana, S; Akhtar, M M; Alam, T; Hossain, S; Meem, A M; Lubaba, A F; Khandoker, M A M Y (Bangladesh Journal of Animal Science, 2026)
Morphometric and histochemical studies provide valuable insights into the structural and functional characteristics of reproductive organs of animals. The experiment was conducted with the aim to evaluate the morphometry of ewe reproductive organs in relation to age and to investigate the effect of age on the histological structure of the ovary, oviduct and uterus. From 9 (nine) reproductive organs of ewe 18 ovaries, 18 oviducts, 18 horns of uterus and 9 uterine bodies were obtained from the local abattoir of Mymensingh municipality, Bangladesh and then categorized based on age (confirmed through dentition pattern and butcher’s report) into two categories: 1-2 years and 2.5-4 years. In the morphometric study, the weight, length and width of ovary, oviduct, body of the uterus, and uterine horns were significantly higher (p<0.05) in ewes aged 2.5-4 years, except for the weight of the ovary and the length and width of the oviduct, which did not differ significantly (p>0.05). In the histological study of ovary, the number of normal primordial, primary, secondary, and antral follicles were non-significantly (p>0.05) higher in ewes at the age of 2.5-4 years than 1-2 years. In case of thickness of layer in oviduct, the serosa and mucosal folds were non-significantly (p>0.05) thicker in the older age compared to the younger group. However, the muscularis layer was significantly (p<0.05) thicker in the older age group (46.42±5.70 μm) than in the younger group (30.97±3.91 μm). In the uterine horn, all assessed layers (perimetrium, myometrium, and endometrium) increased with age. Significant differences were found in the perimetrium and myometrium, but not in endometrial thickness. Within the body of the uterus, all layers were thicker in the older age group, with highly significant differences observed in the myometrium (982.46±8.93 μm vs. 648.50±9.75 μm) and endometrium (1174.79±54.1 μm vs. 697.41±63.0 μm), while the perimetrium also showed a significant increase (43.89±5.73 μm vs. 23.51±3.71 μm). These findings indicate that age significantly influences morphometric characteristics and histological structure of ewe’s reproductive organ, which may have implications for reproductive performance and productivity. Bangladesh Journal of Animal Science 54 (4): 66-73, 2025